2012
DOI: 10.1371/journal.pone.0033766
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of miR-29 by TGF-beta-Smad3 Signaling through Dual Mechanisms Promotes Transdifferentiation of Mouse Myoblasts into Myofibroblasts

Abstract: MicroRNAs (miRNAs) are non-coding RNAs that regulate gene expression in post-transcriptional fashion, and emerging studies support their importance in regulating many biological processes, including myogenic differentiation and muscle development. miR-29 is a promoting factor during myogenesis but its full spectrum of impact on muscle cells has yet to be explored. Here we describe an analysis of miR-29 affected transcriptome in C2C12 muscle cells using a high throughput RNA-sequencing platform. The results rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(114 citation statements)
references
References 39 publications
2
105
1
6
Order By: Relevance
“…To test this notion, we depleted Dum in mouse limb muscles during injury-induced regeneration using intramuscular injection of siRNA oligos as described before [17][18][19]. As illustrated in Figure 3A, the injection of siDum or negative control oligos was performed three times on days 1/4, 2 and 4 post CTX injection and muscles were harvested at the designated times for analyses.…”
Section: Loss Of Dum Delayed Ctx-induced Muscle Regeneration In Vivomentioning
confidence: 99%
“…To test this notion, we depleted Dum in mouse limb muscles during injury-induced regeneration using intramuscular injection of siRNA oligos as described before [17][18][19]. As illustrated in Figure 3A, the injection of siDum or negative control oligos was performed three times on days 1/4, 2 and 4 post CTX injection and muscles were harvested at the designated times for analyses.…”
Section: Loss Of Dum Delayed Ctx-induced Muscle Regeneration In Vivomentioning
confidence: 99%
“…Promoter region of mouse miR-29b-2/c contains four E-box binding sites for MyoD with close proximity to SBE. Independently of these sites the CCAT box binding YY1 is located 22 . MyoD is a transcriptional factor influencing differentiation of skeletal muscle cells 23 .…”
Section: Regulation Of Mir-29 Expressionmentioning
confidence: 99%
“…If Smad3 is not activated by TGF-β, MyoD would bind to the promoter E-box and transcription of miR-29 follows. Therefore TGF-β-Smad3 signaling pathway modulates the miR-29 expression by two mechanisms 22 . Post-transcriptional manner of miR-29 regulation was observed in HeLa cells.…”
Section: Regulation Of Mir-29 Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the number of myofibroblasts, which are partially transformed from fibroblasts and are the real effectors of fibrosis, increased significantly after tail vein injection of anti-miR-29b. Zhou et al 30 provided further evidence for a role of miR-29 in the development of fibrosis after myocardial infarction. Their study showed downregulation of miR-29 in response to overexpression of TGF-β via activation of Smad2 and Smad3, transcription factors that transduce extracellular TGF-β from cell membrane to cytoplasm.…”
Section: Mir-29mentioning
confidence: 96%